2019
DOI: 10.15171/jcs.2019.008
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Anxiolytic Effect of Aromatherapy during the First Stage of Labor

Abstract: Introduction: Anxiety is the most common psychological response of women to labor. The aim of the present systematic review was to evaluate and summarize the available clinical evidence on the anxiolytic effects of aromatherapy during the first stage of labor. Methods: Electronic databases including: Cochrane Library, MEDLINE/ PubMed, Scopus, CINAHL, SID, Iran Doc, ProQuest, and Google Scholar were searched up to Sep10, 2017 with the keywords of 'aroma*', 'aromatherapy', 'essential oil', 'anxiety', and ' labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 25 publications
1
23
0
15
Order By: Relevance
“…They suggested a positive effect on anxiety with a qualitative analysis of the benefit from individual aroma essence oils in the first stage of labor. This previous review also did not perform a meta-analysis, thus this review was not conclusive [7]. Moreover, Ghiasi et al included trials of aromatherapy intervention with massage.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…They suggested a positive effect on anxiety with a qualitative analysis of the benefit from individual aroma essence oils in the first stage of labor. This previous review also did not perform a meta-analysis, thus this review was not conclusive [7]. Moreover, Ghiasi et al included trials of aromatherapy intervention with massage.…”
Section: Discussionmentioning
confidence: 96%
“…In the present review, there was insufficient evidence regarding the effect of reducing anxiety of the participants using inhalation aromatherapy during labor. Ghiasi et al reported the systematic review on the anxiolytic effect of aromatherapy during the first stage of labor [7]. They suggested a positive effect on anxiety with a qualitative analysis of the benefit from individual aroma essence oils in the first stage of labor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of action of the plant’s ingredients, however, is not fully elucidated. Anxiolytic and hypnotic effects are seemingly due to the combination of the action of the plant’s aroma on the limbic system through olfaction and the direct action of terpenes on GABAergic and serotoninergic (5-HT 1A ) receptors [ 39 , 202 , 203 ].…”
Section: Discussionmentioning
confidence: 99%